Uncover the reasons behind customers' choice of Thailand Islamic banks - Bakhri, Boy Syamsul; Ramli, Mona Fairuz bt; Wan Daud, Wan Mohd Nazri (al-Uqud : Journal of Islamic Economics, 2023)
Most religions in Thailand are Buddhists. However, Thailand has four provinces, most of which are Malays or Muslims. This study was motivated by the demographic background and curiosity about Islamic banking services in Thailand. This study examines customer knowledge of products and service facilities in Islamic banking, why customers choose Islamic banks, and why customers use both types of bank (Islamic and conventional banking). This study was a field research using a survey technique to collect data. The population in Thailand is an Islamic bank. The data analysis technique used descriptive statistics with frequency distribution. The study results found that many Islamic bank customers still need to learn about Islamic bank products, such as musyarakah products, mudharabah products, ijarah products, and rahn services. Customers choose Islamic banks primarily for religious reasons, while ease of access to more branches is the main reason for using Islamic and conventional banks. Customers expressed satisfaction with the services provided by Islamic banks, particularly the name and image of the bank, the friendliness and skills of its employees, the confidentiality of customer data, and the variety of facilities offered by the bank. Banks need to improve their services and add touchpoints so that Muslim customers can use Islamic banks and leave conventional banks. In addition, banks are advised to continue educating consumers to understand the importance of Islamic banking, according to Sharia.